Corporate CO₂ offsetting in small- and medium-seized firms in Germany - Daniel Engler; Gunnar Gutsche; Amantia Simixhiu; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2021)
Voluntary CO2 offsetting by individuals, firms, and organizations is increasingly considered as a direction of climate policy that is complementary to traditional approaches such as sub-sidies or CO2 taxes. Based on data from a large-scale survey among corporate decision mak-ers, this paper empirically examines corporate CO2 offsetting and its determinants in small- and medium-sized firms in Germany. Our descriptive analysis shows both a rather limited engagement in corporate CO2 offsetting as well as a strong lack of knowledge about its mechanism. The econometric analysis reveals that some firm-specific characteristics like the average age of the employees, firm size, and firm age matter for CO2 offsetting. However, the main estimation results refer to the relevance of general environment-related variables like the implementation of environmental product and service innovations or the share of employees that carry out environment-related tasks and especially of climate-related factors and activities. In particular, the implementation of climate targets and the participation in the EU Emissions Trading System (EU ETS) are strongly significantly positively correlated with CO2 offsetting. In line with similar findings at the individual level, these estimation results imply that corporate CO2 offsetting also does not substitute or crowd out other climate pro-tection and further pro-environmental activities, but rather complements them.
Keywords: 330; Corporate CO2 offsetting; corporate climate protection and pro-environmental activities; small- and medium-sized firms